Analysis on the MRI and BAEP Results of Neonatal Brain With Different Levels of Bilirubin - Lu, Zhongxing; Ding, Shouling; Wang, Fen; Lv, Haitao (Frontiers in Pediatrics, 2022)
Objective: To provide an objective basis for early diagnosis of subclinical brain injury caused by bilirubin through investigating whether there are abnormalities in brain magnetic resonance imaging (MRI) and brainstem auditory evoked potential (BAEP) results for neonates with different levels of bilirubin. Methods: The clinical data of 103 neonatal patients were retrospectively analysed, including the results of routine brain MRI examinations and BAEP testing. Based on concentration levels of total serum bilirubin (TSB), the neonatal patients were divided into three groups: a mild group (16 patients; TSB = 0.0~229.0 ěmol/L), a moderate group (49 patients; TSB = 229.0~342.0 ěmol/L), and a severe group (38 patients; TSB ≥ 342.0 ěmol/L). Results: The findings were as follows. A) There was a statistically significant difference between neonatal bilirubin levels for the different groups (P<0.01): mild group = 171.99 ± 33.50 ěmol/L, moderate group = 293.98 ± 32.09 ěmol/L, severe group = 375.59 ± 34.25 ěmol/L. B) The weight values of the <2,500g and ≥2,500g groups were 2.04 ± 0.21 and 3.39 ± 0.46, respectively. The weight comparison of the two groups thus indicated a statistically significant difference (P<0.01). C) Comparison of the abnormal MRI of the different groups: the proportions of abnormal brain MRI results were 31.25%, 16.33% and 21.05% in the mild, moderate and severe groups, respectively. The comparison of these results indicated that the differences were not statistically significant (P>0.05). D) Comparison of abnormal MRI signal values of globus pallidus (GP) on T1WI in different groups: comparison of normal group signal values with those for the three sample groups indicated statistically significant differences (P < 0.05 for the mild group and P < 0.01 for the moderate and severe groups). Conclusion: Central nervous system damage may occur even at low bilirubin levels, which can be detected as abnormalities using MRI and BAEP scanning. In addition, MRI and BAEP can provide early abnormal information for the assessment of central nervous system damage of children with neonatal hyperbilirubinemia who have no acute bilirubin encephalopathy clinical features and can provide clues for early treatment and early intervention.